Molecular dynamic simulation on the thermal conductivity of nanofluids in aggregated and non-aggregated states - Lee, S.L.; Saidur, R.; Sabri, M.F.M.; Min, T.K. (Taylor & Francis, 2015)
Nanofluids are engineered by suspending nanoparticles in convectional heat transfer fluids to enhance thermal conductivity. This study is aimed at identifying the role of nanoparticle aggregation in enhancing the thermal conductivity of nanofluids. Molecular dynamic simulation with the Green Kubo method was employed to compute thermal conductivity of nanofluids in aggregated and non-aggregated states. Results show that the thermal conductivity enhancement of nanofluids in an aggregated state is higher than in a non-aggregated state, by up to 35. The greater enhancement in aggregated nanofluids is attributed to both higher collision among nanoparticles and increases in the potential energy of nanoparticles.